Prairie Power : Voices of 1960s Midwestern Student Protest - Lieberman, Robbie, 1954- (Book collections on Project MUSE., 2004)
"Prairie Power, a collection of oral histories from the 1960s, focuses on former student radicals at the University of Missouri, the University of Kansas, and Southern Illinois University. Robbie Lieberman presents a view of midwestern New Left activists that has been neglected in previous studies." "Scholarship on the sixties has been shifting from a national focus to more local and regional studies, but few authors have studied the student movement in the Midwest. Moreover, the characterization of prairie power activists as "long-haired, dope-smoking anarchists" who were responsible for the downfall of Students for a Democratic Society (SDS) has not been challenged directly. While still viewing these activists critically, Lieberman argues that midwestern students made significant contributions to the New Left in the latter half of the decade, and that their efforts were not only important at the time but also had a lasting impact on the universities and towns in which they were active."--Jacket